2020
DOI: 10.1113/ep088931
|View full text |Cite
|
Sign up to set email alerts
|

Sleep restriction alters physiological and emotional responses to emotion induction

Abstract: Habitual insufficient sleep has long-term health consequences via its impact on autonomic nervous system (ANS) function and on regulation of emotion. To our knowledge, the effects of insufficient sleep on emotion-induced ANS function have not been tested. The present study aimed to address this lacuna. Using an emotion induction procedure, the effects of sleep restriction on physiological responses to validated neutral and sad film clips were assessed in a two-by-two, pseudo-randomized, crossover design. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…In general, it is repeatedly suggested that people in the modern society do not sleep enough (Chattu et al, 2018) and that disturbed and insu cient sleep can lead to a wide range of problems and pathologies ranging from increased chances for heart disease (Shi et al, 2021) to heightened emotional susceptibility (Hairston & Cohen-Zion, 2020). Within the range of sleep problems and disturbances, life in the modern world were repeatedly associated with insu cient sleep (CDC, 2012;Chattu et al, 2018) and insu cient sleep and other circadian and sleep disturbances had been repeatedly associated with a large variety of signi cant adverse effects ranging from somatic to mental diseases including (but not limited to) diabetes, hypercholesterolemia, heart disease, depression and more (Chattu et al, 2018;Shi et al, 2021;Zimmet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is repeatedly suggested that people in the modern society do not sleep enough (Chattu et al, 2018) and that disturbed and insu cient sleep can lead to a wide range of problems and pathologies ranging from increased chances for heart disease (Shi et al, 2021) to heightened emotional susceptibility (Hairston & Cohen-Zion, 2020). Within the range of sleep problems and disturbances, life in the modern world were repeatedly associated with insu cient sleep (CDC, 2012;Chattu et al, 2018) and insu cient sleep and other circadian and sleep disturbances had been repeatedly associated with a large variety of signi cant adverse effects ranging from somatic to mental diseases including (but not limited to) diabetes, hypercholesterolemia, heart disease, depression and more (Chattu et al, 2018;Shi et al, 2021;Zimmet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%